E-056 Angiographic and clinical outcomes from 302 aneurysms treated with the pipeline flex embolization device with shield technology: subgroup analysis aad follow-up to pedestrian. (23rd July 2022) - Lylyk, I; Scrivano, E; Lundquist, J; Bleise, C; Perez, N; Nella Castro, R; Lylyk, P; Lylyk, P
Abstract : Background: The PEDESTRIAN registry demonstrated high rates of complete long-term occlusion and good clinical outcomes among patients with intracranial aneurysms treated with the Pipeline Embolization Device. The Pipeline Flex Embolization Device with Shield Technology (PED-Shield) was introduced to minimize thromboembolic complications. In this study, we investigated the safety and effectiveness of PED-Shield among all patients treated for intracranial aneurysms at our center. Methods: This was a single-arm retrospective study of prospectively collected data of patients treated with PED-Shield at our high-volume center between January 2018-January 2021. The primary efficacy endpoint was complete occlusion as measured by a class 1 Raymond-Roy score at 1-year and 2-year follow-up. The primary safety endpoint was major morbidity and neurological mortality up to 1 year following operation. Results: A total of 238 patients (mean age 55.4±14.7 years; 81.1% female), 80 of whom were previously included in PEDESTRIAN, with 302 aneurysms, were analyzed. A total of 268 devices were deployed, with 94.7% (286/302) of aneurysms requiring only one device. Follow-up angiography was available for 82.8% (250/283) of the procedures after a mean time of 12.7 months. Complete occlusion was demonstrated for 75.1% (171/226) of aneurysms at 12 months and 92.5% (62/67) at 24 months. The overall rates of major morbidity and neurological mortality after 2 years were 1.7% (4/238) and 0.4% (1/238), respectively. Conclusion: Our results demonstrate high rates of complete long-term occlusion among patients treated with PED-Shield. We also observed low rates of mortality and morbidity consistent with fewer thromboembolic complications with PED-Shield. Disclosures: I. Lylyk: None. E. Scrivano: None. J. Lundquist: None. C. Bleise: None. N. Perez: None. R. Nella Castro: None. P. Lylyk: None. P. Lylyk: 2; C; Medtronic.